Pulmonary embolism and acute pancreatitis: Case series and review - Robert Deiss; Phillip Young; James Yeh; Sofiya Reicher (Turkish Journal of Gastroenterology, 2019)
Reports of pulmonary embolism in the setting of acute pancreatitis are rare. We present three cases of acute pancreatitis associated with pulmonary embolism and review the literature. Two of the three patients had severe acute pancreatitis with bilateral pulmonary emboli, and to our knowledge, these cases represent the first report of pulmonary embolism occurring in the setting of pancreatic ascites and pleural effusion. All patients experienced abdominal pain, though in one patient, symptoms suggestive of a pulmonary embolism were lacking. All three patients were successfully treated with unfractionated heparin and conservative management. Pulmonary thrombosis may occur in the setting of severe acute pancreatitis as the result of systemic inflammatory response. We review the literature and provide microvascular explanations for the occurrence of pulmonary complications and thrombosis in the setting of acute pancreatitis. We also review prior cases of pulmonary embolism in acute pancreatitis. Our experience suggests that pulmonary embolism may be an under-recognized complication of severe acute pancreatitis.